Amino acids as possible alternative nitrogen source for growth of Euglena gracilis Z in life support systems - Richter, Peter; Liu, Y.; An, Y.; Li, X.; Nasir, Adeel; Strauch, Sebastian; Becker, Ina; Krüger, Julia; Schuster, Martin; Ntefidou, Maria; Daiker, Viktor; Haag, Ferdinand; et al. (Life Sciences in Space Research, 2015)
In recent times Euglena gracilis Z was employed as primary producer in closed environmental life-support system (CELSS), e.g. in space research. The photosynthetic unicellular flagellate is not capable of utilizing nitrate, nitrite, and urea as nitrogen source. Therefore, ammonium is supplied as an N-source in the lab (provided as diammonium-dihydrogenphosphate, (NH)HPO) to E. gracilis cultures. While nitrate exerts low toxicity to organisms, ammonium is harmful for many aquatic organisms especially, at high pH-values, which causes the ionic NH4+ (low toxicity) to be partially transformed into the highly toxic ammonia, NH. In earlier reports, Euglena gracilis was described to grow with various amino acids as sole N-source. Our aim was to investigate alternatives for (NH)HPO as N-source with lower toxicity for organisms co-cultivated with Euglena in a CELSS. The growth kinetics of Euglena gracilis cultures was determined in the presence of different amino acids (glycine, glutamine, glutamic acid, leucine, and threonine). In addition, uptake of those amino acids by the cells was measured. Cell growth in the presence of glycine and glutamine was quite comparable to the growth in (NH)HPO containing cultures while a delay in growth was observed in the presence of leucine and threonine. Unlike, aforementioned amino acids glutamate consumption was very poor. Cell density and glutamate concentration were almost unaltered throughout the experiment and the culture reached the stationary phase within 8 days. The data are compared with earlier studies in which utilization of amino acids in Euglena gracilis was investigated. All tested amino acids (glutamate with limitations) were found to have the potential of being an alternative N-source for Euglena gracilis. Hence, these amino acids can be used as a non-toxic surrogate for (NH)HPO.
Keywords: Amino-acids; CELSS; Euglena gracilis; Nitrogen source

Eu:CROPIS - "Euglena gracilis: Combined Regenerative Organic-food Production in Space" - A Space Experiment Testing Biological Life Support Systems Under Lunar And Martian Gravity - Hauslage, Jens; Strauch, Sebastian; Essmann, Olaf; Haag, Ferdinand; Richter, Peter; Krüger, Julia; Stoltze, Julia; Becker, Ina; Nasir, Adeel; Bornemann, Gerhild; Mueller, Hartmut; Delovski, Toni; et al. (Microgravity Science and Technology, 2018)
Human space exploration needs stable life support systems for the supply of oxygen, water and food for each human explorer due to long term missions. The most promising approach for building stable life support systems is a combination of physico-chemical and biological systems. These hybrid systems combine the reliability of physico-chemical and the sustainability of biological life support systems. Also the disadvantages, which are the finite resources of physico-chemical and the imperfect reliability of biological systems, are mutually balanced. To improve the reliability of biological life support systems, a combination of different biological systems may stabilize the whole approach during long term operations. The satellite mission Eu:CROPIS (Euglena gracilis: Combined Regenerative Organic-food Production In Space) is a testbed for investigating the behavior of combined biological life support systems under the influence of altered gravity, here, Lunar and Martian gravity. The core systems are a biological trickle filter for processing urine into a fertilizer solution via nitrification and Euglena gracilis, a photosynthetic protist which is able to produce oxygen and biomass while protecting the whole system against high ammonia concentrations.
Keywords: Compact satellite; Life support system; Moon; Mars; Reduced gravity; Nitrification

Evaluation of the adverse effects of two commonly used fertilizers, DAP and urea, on motility and orientation of the green flagellate Euglena gracilis - Azizullah, Azizullah; Nasir, Adeel; Richter, Peter; Lebert, Michael; Häder, Donat-Peter (Environmental and Experimental Botany, 2011)
The effect of two commonly used fertilizers, DAP (diammonium phosphate) and urea was studied on the freshwater flagellate Euglena gracilis using the automatic biotest ECOTOX. NOEC and EC(50) values for various parameters like motility, velocity, cell shape and gravitaxis were calculated. The NOEC and EC(50) values obtained for DAP were much lower than those for urea; i.e. DAP showed a stronger inhibitory effect as compared to urea. The inhibition caused by DAP increased with increasing exposure time over 24 h but urea showed no augmentation with increasing exposure time. Application of DAP resulted in an increased pH and high concentrations of ammonia but urea did neither affect the pH nor affect the ammonia concentration. Recovery experiments in deionized water after urea application showed a reconstitution of motility after 72 h. After an application of 1.35 g L(-1) (24 h EC(50) for motility) DAP motility recovered after 72 h but motility did not recover when the concentration was doubled (2.7 g L-1). The EC(50) values obtained were compared with the EC(50)/LC(50) values reported for other aquatic organisms and were found to be comparable with the reported values. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: DAP; Urea; ECOTOX; Euglena gracilis; Motility; Gravitaxis

Influence of Different Light-Dark Cycles on Motility and Photosynthesis of Euglena gracilis in Closed Bioreactors - Richter, Peter; Strauch, Sebastian; Ntefidou, Maria; Schuster, Martin; Daiker, Viktor; Nasir, Adeel; Haag, Ferdinand; Lebert, Michael (Astrobiology, 2014)
The unicellular photosynthetic freshwater flagellate Euglena gracilis is a promising candidate as an oxygen producer in biological life-support systems. In this study, the capacity of Euglena gracilis to cope with different light regimes was determined. Cultures of Euglena gracilis in closed bioreactors were exposed to different dark-light cycles (40 W/m(2) light intensity on the surface of the 20 L reactor; cool white fluorescent lamps in combination with a 100 W filament bulb): 1 h-1 h, 2 h-2 h, 4 h-4 h, 6 h-6 h, and 8 h-16 h, respectively. Motility and oxygen development in the reactors were measured constantly. It was found that, during exposure to light-dark cycles of 1 h-1 h, 2 h-2 h, 4 h-4 h, and 6 h-6 h, precision of gravitaxis as well as the number of motile cells increased during the dark phase, while velocity increased in the light phase. Oxygen concentration did not yet reach a plateau phase. During dark-light cycles of 8 h-16 h, fast changes of movement behavior in the cells were detected. The cells showed an initial decrease of graviorientation after onset of light and an increase after the start of the dark period. In the course of the light phase, graviorientation increased, while motility and velocity decreased after some hours of illumination. In all light profiles, Euglena gracilis was able to produce sufficient oxygen in the light phase to maintain the oxygen concentration above zero in the subsequent dark phase. Key Words: Euglena gracilis-Bioreactor-Light-dark cycle-Motility-Gravitaxis. Astrobiology 14, 848-858.

Molecular Cross-Talk between Gravity-and Light-Sensing Mechanisms in Euglena gracilis - Nasir, Adeel; Richter, Peter; le Bail, Aude; Daiker, Viktor; Stoltze, Julia; Prasad, Binod; Strauch, Sebastian Michael; Lebert, Michael (International Journal of Molecular Sciences, 2022)
Euglena gracilis is a photosynthetic flagellate. To acquire a suitable position in its surrounding aquatic environment, it exploits light and gravity primarily as environmental cues. Several physiological studies have indicated a fine-tuned relationship between gravity sensing (gravitaxis) and light sensing in E. gracilis. However, the underlying molecular mechanism is largely unknown. The photoreceptor photoactivated adenylyl cyclase (PAC) has been studied for over a decade. Never-theless, no direct/indirect interaction partner (upstream/downstream) has been reported for PAC. It has been shown that a specific protein, kinase A (PKA), showed to be involved in phototaxis and gravitaxis. The current study reports the localization of the specific PKA and its relationship with PAC.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Euglena gracilis; Gravitaxis; Indirect immuno-fluorescent assay; Movement analysis; Photoactivated adenylyl cyclase; Phototaxis; Protein kinase A; RNA interference

The influence of microgravity on Euglena gracilis as studied on Shenzhou 8 - Nasir, Adeel; Strauch, Sebastian; Becker, Ina; Sperling, Anna; Schuster, Martin; Richter, Peter; Weißkopf, Matthias; Ntefidou, Maria; Daiker, Viktor; An, Y. A.; Li, X. Y.; Liu, Y. D.; et al. (Plant Biology, 2014)
The German Aerospace Center (DLR) enabled German participation in the joint space campaign on the unmanned Shenzhou 8 spacecraft in November 2011. In this report, the effect of microgravity on Euglena gracilis cells is described. Custom-made dual compartment cell fixation units (containing cells in one chamber and fixative - RNA lysis buffer - in another one) were enclosed in a small container and placed in the Simbox incubator, which is an experiment support system. Cells were fixed by injecting them with fixative at different time intervals. In addition to stationary experiment slots, Simbox provides a 1g reference centrifuge. Cell fixation units were mounted in microgravity and 1g reference positions of Simbox. Two Simbox incubators were used, one for space flight and the other as ground reference. Cells were fixed soon after launch and shortly before return of the spaceship. Due to technical problems, only early in-flight samples (about 40min after launch microgravity and corresponding 1g reference) were fully mixed with fixative, therefore only data from those samples are presented. Transcription of several genes involved in signal transduction, oxidative stress defence, cell cycle regulation and heat shock responses was investigated with quantitative PCR. The data indicate that Euglena cells suffer stress upon short-term exposure to microgravity; various stress-induced genes were up-regulated. Of 32 tested genes, 18 were up-regulated, one down-regulated and the rest remained unaltered. These findings are in a good agreement with results from other research groups using other organisms.
Keywords: Euglena gracilis; gene expression; microgravity; qPCR; space flight; unicellular flagellate

What an Escherichia coli Mutant Can Teach Us About the Antibacterial Effect of Chlorophyllin - Krueger, Marcus; Richter, Peter; Strauch, Sebastian; Nasir, Adeel; Burkovski, Andreas; Antunes, Camila A.; Meißgeier, Tina; Schlücker, Eberhard; Schwab, Stefan; Lebert, Michael (Microorganisms, 2019)
Due to the increasing development of antibiotic resistances in recent years, scientists search intensely for new methods to control bacteria. Photodynamic treatment with porphyrins such as chlorophyll derivatives is one of the most promising methods to handle bacterial infestation, but their use is dependent on illumination and they seem to be more effective against Gram-positive bacteria than against Gram-negatives. In this study, we tested chlorophyllin against three bacterial model strains, the Gram-positive Bacillus subtilis 168, the Gram-negative Escherichia coli DH5 alpha and E. coli strain NR698 which has a deficient outer membrane, simulating a Gram-negative "without" its outer membrane. Illuminated with a standardized light intensity of 12 mW/cm(2), B. subtilis showed high sensitivity already at low chlorophyllin concentrations (<= 10(5) cfu/mL: <= 0.1 mg/L, 10(6)-10(8) cfu/mL: 0.5 mg/L), whereas E. coli DH5 alpha was less sensitive (<= 10(5) cfu/mL: 2.5 mg/L, 10(6) cfu/mL: 5 mg/L, 10(7)-10(8) cfu/mL: ineffective at <= 25 mg/L chlorophyllin). E. coli NR698 was almost as sensitive as B. subtilis against chlorophyllin, pointing out that the outer membrane plays a significant role in protection against photodynamic chlorophyllin impacts. Interestingly, E. coli NR698 and B. subtilis can also be inactivated by chlorophyllin in darkness, indicating a second, light-independent mode of action. Thus, chlorophyllin seems to be more than a photosensitizer, and a promising substance for the control of bacteria, which deserves further investigation.
CRIS-Team WoS Importer:2019-03-15